460 Integrating pharmacist independent prescribing in community pharmacy: investigating NHS Pharmacy First Plus using Normalization Process Theory. (13th April 2023) - Karim, L; McIntosh, T; Pfleger, D; Osprey, A; Cunningham, S
Abstract: Introduction: Limited evidence exists for independent prescribing in community pharmacy (CP) (1). In 2020 NHS Scotland launched NHS Pharmacy First Plus (PFP), aiming to facilitate access to pharmacist independent prescribers (PIPs) in CP, focusing on common clinical conditions. Aim: To investigate, using Normalization Process Theory (NPT), the integration of PIPs in CP in the context of NHS PFP. Methods: A cross-sectional online survey of all 120 community pharmacists offering PFP in 13 Scottish NHS Health Boards. A 'Think Aloud' tested, pre-piloted questionnaire was developed using the NPT derived NoMAD tool (2) and including demographic and practice characteristic questions for contextualisation. This was disseminated via email with 3 reminders. Data exported from Online Surveys (JISC) to SPSS was analysed descriptively. Scale score statistics for each of the four NPT constructs (Table 1) were calculated through summation of item scores (5 = Strongly agree to 1 = Strongly disagree) for each respondent with scale item reliability testing using Cronbach's alpha. Results: A 73% (88/120) response rate showed the majority were female (63%, 55/88), <40 years old (51%, 45/88), had worked in CP for >15 years (56%, 49/88) and qualified as a PIP <5 years ago (59%, 52/88). 76% (67/88) indicated on average they consulted with patients under PFP >6 times a week. 38% (33/88) indicated they had <3 staff when offering PFP and 47% (41/88) indicated that they provided the service while working as the only pharmacist; 35% (25/71) had one other pharmacist. Generally, there were high levels of NoMAD item agreement with >90% 'strongly agreeing' or 'agreeing' in items relating to 'coherence', 'cognitive participation' and 'reflexive monitoring'. Responses to 'collective action' items showed diversity with more answering 'neither agree nor disagree' or 'disagree'. Conclusion: This theory-based work with an excellent response rate offers a robust and unique perspective on PIP integration within CP. The positivity could perhaps be expected from trailblazer respondents but it also highlights challenges within the 'collective action' construct and a need to focus on training, staff resource, working relationships and management. More work is planned on scale score inferential analysis and qualitative exploration of key findings. References: 1. Weeks G, George J, Maclure K et al. Non-medical prescribing versus medical prescribing for acute and chronic disease management in primary and secondary care. Cochrane Database Syst Rev. 2016; 11: CD011227 2. Finch, T.L., Girling, M., May, C.R. et al. Improving the normalization of complex interventions: part 2 - validation of the NoMAD instrument for assessing implementation work based on normalization process theory (NPT). BMC Med Res Methodol 18, 135 (2018). https://doi.org/10.1186/s12874-018-0591-x ]